Role of halide ions and temperature on the morphology of biologically synthesized gold nanotriangles - Rai, A.; Singh, A.; Ahmad, Absar; Sastry, M. (Langmuir, 2006)
{In this paper, we demonstrate the effect of halide ions on the formation of biogenically prepared gold nanotriangles using the leaf extract of lemongrass (Cymbopogonflextiosus) plant. We have also studied the effect of halide ions on the morphology of biogenic nanotriangles. It has been shown that iodide ions have a greater propensity to transform flat gold nanotriangles into circular disklike structures as compared to other halide ions. The study also suggests that the presence of Cl- ions during the synthesis promotes the growth of nanotriangles, whereas the presence of I- ions distorts the nanotriangle morphology and induces the formation of aggregated spherical nanoparticles. The change in the morphology of gold nanotriangles has been explained in terms of the ability of the halide ions to stabilize or inhibit the formation of (I 11) faces to form [
Keywords: DME steam reforming; fuel cells; Hydrogen; Mixed oxides; supported Ga2O3; XPS